Entre o campo e a cidade: as territorialidades do distrito de Tapuirama (Uberlândia / MG) 1975-2005 - Montes, Silma Rabelo (2006)
This research aims understand, the meaning of the territorialities from the relation field-city, and the changes sociospacials that took place at Tapuirama district (Uberlândia MG), in the last thirty years, considering the agricultural modernization and urban growing of the Uberlândia. Also it was focused the political, economic and cultural power the Uberlândia city exerts on Triângulo Mineiro/Alto Paranaíba region, and, mainly, on Miraporanga, Martinésia, Cruzeiro dos Peixotos and Tapuirama districts. It was discussed territory ideas, territoriality, municipal district, district, relationship between field-city and territorial fragmentation in order to understand the local reality. It was analyzed the historical formation process an the territorial social economic organization of Uberlândia municipal district, and also of the seat district and their others four districts. The emphasis was given to Tapuirama district with a study about its dynamic sociospacial and urban rural territorialities. Taking into account the rural an urban dimensions and the interaction of field city it was discussed a lot of themes as: changes on the use of the soil and on the laborite relations, the way citizens live the relationships local people face the seat district and, mainly, inhabitants expectations related to the local future.